Conducting Biobehavioral Research in Patients With Advanced Cancer: Recruitment Challenges and Solutions. (October 2017) - Gilbertson-White, Stephanie; Bohr, Nicole; Wickersham, Karen E.
Despite significant advances in cancer treatment and symptom management interventions over the last decade, patients continue to struggle with cancer-related symptoms. Adequate baseline and longitudinal data are crucial for designing interventions to improve patient quality of life and reduce symptom burden; however, recruitment of patients with advanced cancer in longitudinal research is difficult. Our purpose is to describe challenges and solutions to recruitment of patients with advanced cancer in two biobehavioral research studies examining cancer-related symptoms. Study 1: Symptom data and peripheral blood for markers of inflammation were collected from newly diagnosed patients receiving chemotherapy on the first day of therapy and every 3–4 weeks for up to 6 months. Study 2: Symptom data, blood, and skin biopsies were collected from cancer patients taking epidermal growth factor receptor inhibitors at specific time points over 4 months. Screening and recruitment results for both studies are summarized. Timing informed consent with baseline data collection prior to treatment initiation was a significant recruitment challenge for both the studies. Possible solutions include tailoring recruitment to fit clinic needs, increasing research staff availability during clinic hours, and adding recruitment sites. Identifying solutions to these challenges will permit the conduct of studies that may lead to identification of factors contributing to variability in symptoms and development of tailored patient interventions for patients with advanced cancer.